Active controllable and flexible winding needle an option to reduce the complexity of needle winding machines and the stress on enameled wire - Schneider, Michael; Bickel, Benjamin; Risch, Florian; Franke, Jörg (2014 4th International Electric Drives Production Conference, EDPC 2014 - Proceedings, 2014)
State of the art needle winding technologies have one thing in common-a stiff, straight or bent winding needle. During the manufacturing process of electrical machines, the used enameled wires are exposed to deformations which decrease the insulation resistance against partial discharge and disruptive discharge. A reduced insulation resistance shortens the product lifecycle. The active controllable and flexible winding needle is able to adapt its form to the mechanical behavior of wire during any deformation and thus to wind wires more gently. In the production of electrical machines the copper filling factor in the slot is often considered key. To provide the needed space for the tools to move through the stator while distributing the windings, the winding tools have to be rather small or the inner diameter of the stator has a minimum whereat the feasibility for needle winding is still present. With the actively controllable and flexible winding needle no more extra axis and other constructions are necessary to fulfill the requirements of a small tool at maximum flexibility.
CRIS-Team Scopus Importer:2023-03-07
Keywords: distributed winding; winding guide nozzle; winding needle; winding technology

Bewertung neuer Fertigungskonzepte für hohe Stückzahlen in der E-Maschinenfertigung - Bogner, Eva; Bickel, Benjamin; Franke, Jörg (Vorausschau und Technologieplanung, 2015)
Der zunehmende Einsatz von Elektromotoren im Automobilbereich stellt neue Anforderungen an deren Bauweise und die notwendigen Produktionsprozesse. Um auf die wachsenden Absatzpotentiale im Bereich der Elektrofahrzeuge reagieren zu können, bedarf es nicht nur einer Produktoptimierung hinsichtlich Bauraum, Gewicht und Wirkungsgrad, sondern vor allem auch automatisierter, stückzahl- und variantenflexibler Produktionstechnologien. Jedoch entscheiden sich Unternehmen aufgrund der hohen notwendigen Investitionskosten trotz der Potentiale häufig gegen die Investition in neue Technologien. Aus diesem Grund beschäftigt sich dieser Beitrag mit der ganzheitlichen Bewertung neuer Fertigungskonzepte für die E-Maschinenfertigung. Damit soll sowohl ein Wirtschaftlichkeitsvergleich hinsichtlich hoher Stückzahlen ermöglicht als auch die technologischen Nutzenpotentiale der Konzepte nachvollziehbar offengelegt werden. Herausforderung ist dabei neben der Strukturierung der komplexen Entscheidungssituation die Erarbeitung eines Gesamtsystems zur Integration und Darstellung der Gesamtergebnisse, das eine gezielte Abwägung zwischen den Potentialen und Kosten neuer Technologien ermöglicht. Zur Durchführung der Bewertung dient ein Tool, das die entwickelte Bewertungsmethodik entsprechend abbildet und einen iterativen Bewertungsprozess sowie die Simulation verschiedener Technologieszenarien ermöglicht. Anwendungsbeispiel ist die Optimierung der Statorfertigung der BMW AG im Rahmen eines öffentlich geförderten Forschungsprojektes. Anhand der gewonnenen Erkenntnisse und deren Interpretation wird eine Handlungsempfehlung für die zukünftige flexible weitestgehend vollautomatisierte Produktion von E-Maschinen abgeleitet.
Keywords: Technologiebewertung; Elektromotoren; Fertigungstechnologien

Development of a control system for a universal winding machine based on virtual path planning - Mahr, Alexander; Wurm, Markus; Bickel, Benjamin; Franke, Jörg; Halder, Hubert (2017 7th International Electric Drives Production Conference (EDPC), 2017)
For the flexible production of increased efficient electric drives new production machines are needed. To this end a new, highly flexible winding machine, which can be used for a broad range of different windings, is presented. The use of two kinematic chains facilitates a higher degree of freedom than conventional machines in this sector. In addition to the mechanical flexibility of the machine, the path planning must be simple and intuitive. The software for path planning is based on the principle of a CAD-CAM chain, as it is also used with robot kinematics. In order to enable these functionalities, a special programming method for PLC- and CNC core is require
Keywords: E|DRIVE; Automated Winding Assembly; Stator; Key Words: Robot-based

Explicit dynamics process simulation of linear coil winding for electric drives production - Bönig, Jochen; Bickel, Benjamin; Spahr, Michael; Fischer, Christian; Franke, Jörg (2014 4th International Electric Drives Production Conference, EDPC 2014, 2014)
Slowly but steadily, more and more electric vehicles push onto the consumer market. For a cost efficient production of electrical engines, in first-class quality and in sufficient quantity, it is indispensable to understand the process of coil winding. Thereby the prediction of the wire behavior is one of the key challenges. Therefore, a detailed model is built to investigate wire behavior during the linear winding process. The finite element based simulation tool LS-DYNA serves as explicit dynamics tool. To represent the high dynamic process of winding within this simulation, some first adaptions have to be made. This means, that dynamic influences such as rotational speed or acceleration of the coil body are definable. Within process simulation, the given boundary conditions are applied to the model. The material properties of the wire under scrutiny are validated by a tensile test and by the values out of datasheets in previous research. In order to achieve the best convergence, different contact algorithms are selected for each individual contact behavior. Furthermore, specific adjustments to the mesh are necessary to gain significant results. State of the art in coil winding is an experimental procedure, which delivers adequate process parameters and, thus, expertise in winding technology. Nevertheless, there are a lot of different, interacting parameters, which have to be optimized in terms of boundary conditions. The simulation model of winding process, in which varying parameters can be optimized pertaining to the optimal winding result, calls for extensive research in this field. The generated model enables the user not only to influence the process parameters but also to modify the geometry of a winding body. To make the simulation scientifically sound, it is validated by previous experiments and simulations
Keywords: coil winding; Explicit dynamics; simulation

Flexible automation for the production of contactless power transfer systems for electric vehicles - Risch, Florian; Günther, Stefan; Bickel, Benjamin; Franke, Jörg (2013 3rd International Electric Drives Production Conference, EDPC 2013 - Proceedings, 2013)
The increasing electrification of the automotive power train leads to significant changes in automotive value chains, while sales potentials are still uncertain [1]. Due to their considerable advantages in regard to safety and convenience, contactless power transfer systems may be the basis for further increasing the customers' acceptance for electrified vehicle concepts [2]. Increasing market acceptance will require high volume production concepts for contactless power transfer systems. Thus, the importance of automated assembly and manufacturing technologies moves into the focus. Especially the winding process of the HF-litz wire coil structures shows potential for further rationalization. Therefore, it is the aim of this paper to present flexible automation concepts for this process. © 2013 IEEE.
CRIS-Team Scopus Importer:2023-03-07
Keywords: contactless power transfer systems; electric vehicles; flexible production concepts; winding of HF-litz wires

Implementation of the Needle Winding Technique for Diamond Coils - Bickel, Benjamin; Mahr, Alexander; Kühl, Alexander; Franke, Jörg; Meixner, Sebastian; Berendt, Emil; Riedel, Andreas (5th International Electric Drives Production Conference, 2015)

Manufacturing Techniques for Improved Electric Traction Drives - Bickel, Benjamin; Mahr, Alexander; Meixner, Sebastian; Bäumler, Markus; Franke, Jörg (Proceeding of the 26th International Conference on Flexible Automation and Intelligent Manufacturing (FAIM), 2016)
The use of electric drives as traction motors in electric vehicles creates new requirements in the well-known business area of industrial electric machines. These include demands for high power at reduced sizes combined with increased efficiency rates. The winding, as the heart of the electric drive, determines the electro-magnetic characteristics of the complete motor for the most part. Consequently, there is the need to optimize the winding design in order to increase the power density and efficiency of the machine. Most highly optimized machines are produced in small batch sizes and require a vast amount of manual work, which increases the time required for and the cost of manufacturing. Thus, the common manufacturing methods must be analyzed and optimized in order to develop efficient drive windings. Alternative solutions for the manufacturing for improved diamond coil windings are reviewed in experiments and evaluated with respect to their advantages within an integral production line.<br

Simulation-Assisted Method for Evaluating Innovative Production Technologies for Electric Traction Motors - Metzner, Maximilian; Bickel, Benjamin; Mayr, Andreas; Franke, Jörg (2018 8th International Electric Drives Production Conference (EDPC), 2018)
Keywords: Production; Traction motors; Synchronous motors; Windings; Investment; Stator cores; technology evaluation; production technology; electric motor; cost-benefit analysis; discrete event simulation

Simulation of orthocyclic windings using the linear winding technique - Bönig, Jochen; Bickel, Benjamin; Spahr, Michael; Fischer, Christian; Franke, Jörg (5th International Conference on Electric Drives Production, EDPC 2015, 2015)
A continuously rising number of electric vehicle licensing is mentioned since the last few years in Germany. For a cost-efficient production of electrical engines in first-class quality and in sufficient quantity, it is indispensable to understand the process of coil winding. Thereby, the prediction of wire behavior is one of the key challenges. Therefore, a detailed model is built to investigate wire behavior during the linear winding process. The finite element based simulation tool LS-DYNA serves as explicit dynamics tool. The tool works with an explicit time integration method for time discretization. To represent the high dynamic process of winding within this simulation, dynamic influences such as rotational speed or acceleration of the coil body are definable. Within process simulation, the given boundary conditions are applied to the model. The non-linear material properties of the wire are validated under scrutiny by a tensile test and by values out of datasheets in previous research work. Simulation results of orthocyclic windings using the linear winding technique are presented within this paper. The dynamic simulation model is validated by experiments using the caster angle of the wire guide as reference parameter. The caster angel rises during the winding process of the first layer until the wire jumps to the next layer. Hence, it is possible to identify the maximum caster angle and match the simulation value against the experiment value. The travel profile of the wire guide is identified as extremely important to generate an orthocyclic winding. Another substantial part is the wire fixation respectively the geometry to support the first winding offset from winding one to winding two. Results of orthocyclic windings are simulated with and without grooves on the coil body surface and demonstrate the positive influence of grooves for an accurate orthocyclic winding picture.
Keywords: Explicit dynamics; linear winding; simulation

Structural mechanics process simulation of linear coil winding - Bönig, Jochen; Bickel, Benjamin; Ebenhöch, Matthias; Spahr, Michael; Fischer, Christian; Franke, Jörg (Trans Tech Publications Ltd, 2014)
Slowly but steadily, more and more electrical vehicles push onto the consumer market. To produce electrical engines cost efficiently, in first-class quality and in sufficient quantity, it is indispensable to understand the process of winding. The prediction of the wire behaviour is one of the key challenges of coil winding. It is sophisticated and sometimes impossible to measure relevant process parameters (like the wire pull force after wire guide, the wire stress after deformation) in experiments in order to be able to investigate the process in detail. Therefore, a detailed model is built to simulate the wire behaviour during linear winding process. The finite element based simulation tool ANSYS Workbench® serves as the static structural component tool. ANSYS provides comprehensive possibilities in structural mechanics and it is possible to simulate thermal and electrical physics for future work (Co-simulation within one tool). To represent the high dynamic process of winding within this simulation, some first adaptions have to be made. This means, that dynamic influences such as rotational speed or acceleration of the coil body are neglected. Within static structural analysis, the given boundary conditions are applied to the model. The material properties of wires under scrutiny are validated by a tensile test and by the values of datasheets. In order to achieve the best convergence, different contact algorithms are selected for each individual contact behaviour. Furthermore, some adjustments to the mesh are necessary to gain significant results. State of the art in coil winding is an experimental procedure, which delivers good process parameters and, thus, expertise in winding technology. However, there are a lot of different, interacting parameters, which have to be optimized in terms of boundary conditions. The simulation model of the winding process, where varying parameters can be optimized pertaining to the optimal winding result, calls for extensive research in this field. The generated model enables users not only to influence the process parameters but also to modify the geometry of the winding body. To make the simulation scientifically sound, it is validated by experiments.
Keywords: Coil winding; Simulation; Structural analysis

Theoretical benefits of powder-coating based insulation layers regarding copper fill factor in electric drives - Hofmann, Benjamin; Bickel, Benjamin; Bräuer, Philipp; Leder, Michael; Franke, Jörg (6th International Electric Drives Production Conference (EDPC), 2016)
Keywords: E|DRIVE